Commute quality and its implications for commute satisfaction: Exploring the role of mode, location, and other factors. (July 2019) - Handy, Susan; Thigpen, Calvin
Highlights: We examine three dimensions of commute quality: stress, wasted time, and liking. Bicycle and train commuters report the highest quality commutes, bus riders the lowest. Commute quality is strongly associated with overall commute satisfaction. Increasing the opportunity to live near work would increase commute quality and satisfaction. Abstract: The quality of a worker's commute significantly impacts her well-being. We seek to add to the nascent literature on this topic by examining how travel mode, location, and other personal characteristics are associated with perceived commute quality and then by exploring implications for commute satisfaction. We use data from the annual Campus Travel Survey of students and employees at the University of California, Davis and focus on three dimensions of the commute experience: how stressful the commute to campus is, whether travel time is seen as wasted time, and the degree to which commuters like their travel mode. Our analysis shows that commute quality differs by residential location, commute mode, student versus employee status, and gender. Overall, bicycle commuters and train commuters report the highest quality commutes, all else equal; bus riders report the lowest quality commutes; the results for those traveling to campus by car are somewhere in the middle. We also find that all three dimensions of perceived commute quality are strongly associated with overall commute satisfaction. These results point to several different strategies for employers like UC Davis that aim to improve commute quality in order to enhance well-being: improve the quality of each mode, encourage a shift to modes offering higher quality commutes, identify "mis-matched" employees who are not using the mode that would yield the highest commute satisfaction, use social marketing techniques to change perceptions of and preferences for commute options, and increase housing near work sites to enable more commuters to live within bicycling distance.